2014
DOI: 10.1590/1678-41627002
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de anticorpos anti-Neospora spp. em jumentos (Equus asinus) no estado de Sucre - Colômbia

Abstract: RESUMOA neosporose tem grande importância em bovinos, e sua patogênese neste hospedeiro, em termos gerais, está esclarecida, porém, em equídeos é pobremente conhecida. Na Colômbia ainda não foram reportados anticorpos Anti-Neospora spp. em equídeos, sendo assim objetivou-se no presente estudo avaliar a ocorrência do parasito em jumentos (Equus asinus) de fazendas que apresentavam risco da doença nestes animais. Foram utilizados 56 animais no estado de Sucre (Colômbia), escolhidos aleatoriamente dentro das faze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…in donkeys was 11.8% using a competitive-ELISA (MACHACOVÁ et al, 2013) and in Colombia, 11 of the 56 examined donkeys presented antibodies against Neospora spp. measured by Dot-ELISA (BLANCO et al, 2014). Due the different methodology used in the studies, comparisons between these studies and the present study are difficult to make.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…in donkeys was 11.8% using a competitive-ELISA (MACHACOVÁ et al, 2013) and in Colombia, 11 of the 56 examined donkeys presented antibodies against Neospora spp. measured by Dot-ELISA (BLANCO et al, 2014). Due the different methodology used in the studies, comparisons between these studies and the present study are difficult to make.…”
Section: Resultsmentioning
confidence: 83%
“…and S. neurona exposure in donkeys (Equus asinus) from other countries is scarce (MACHACOVÁ et al, 2013;BLANCO et al, 2014). Donkeys are used traditionally for working roles, however in some parts of the world they are increasingly being used for milk production.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the South American studies were conducted in Brazil, with only two out of twelve studies conducted in Colombia. The studies conducted in Colombia reported seroprevalence rates of 1.23% using IFAT assays [25], and one study utilized ELISA assays, reporting a seroprevalence of 19.7% [18].…”
Section: Discussionmentioning
confidence: 99%
“…In another study in Brazil, researchers found antibodies to Neospora in 2 of 500 donkeys studied using IFAT (cut-off 1:100) [ 6 ]. Antibodies to Neospora were also reported in 11 (19.7%) of 56 donkeys from Colombia by using Dot-ELISA [ 2 ], in 52 (52%) of 100 donkeys from Iran by the Neospora agglutination test (NAT, cut-off 1:80) [ 8 ], and 28 (11.8%) of 238 donkeys from Italy by using competitive inhibition ELISA [ 12 ]. Again, comparison of seroprevalences among the studies should be interpreted cautiously because of different laboratory methods used to detect anti- Neospora antibodies.…”
Section: Discussionmentioning
confidence: 99%